1995
DOI: 10.1002/ana.410380119
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent stroke and thrombo‐occlusive events in the antiphospholipid syndrome

Abstract: We prospectively studied 81 consecutively identified patients with antiphospholipid antibodies (aPLs) who developed focal cerebral ischemia over a 7-year period. The mean age of this cohort was approximately a decade younger than the average atherothromboembolic stroke victim and women were more commonly involved than men. The frequency of conventional stroke risk factors was lowest in the group of stroke patients with the highest levels of IgG cardiolipin immunoreactivity. Other serological abnormalities asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(89 citation statements)
references
References 14 publications
1
85
2
1
Order By: Relevance
“…[689][690][691][692][693][694] In a case-control study of 255 patients with a mean age of 66 years, the presence of an anticardiolipin antibody was associated with a significantly increased risk for ischemic stroke (adjusted OR, 2.31; 95% CI, 1.09-4.90). 695 These findings were not replicated in a subsequent prospective cohort study that was part of WARSS.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[689][690][691][692][693][694] In a case-control study of 255 patients with a mean age of 66 years, the presence of an anticardiolipin antibody was associated with a significantly increased risk for ischemic stroke (adjusted OR, 2.31; 95% CI, 1.09-4.90). 695 These findings were not replicated in a subsequent prospective cohort study that was part of WARSS.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…700 Other studies that enrolled older patients or a mixture of young and old patients with ischemic stroke indicated wide variability in the prevalence of antiphospholipid antibodies, from 6% to 46%, and inconsistent findings for an association. [690][691][692][693][694][696][697][698][699]701 The wide variability reflects differences in diagnostic criteria, including persistence.…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%
“…Early studies showed an increased recurrent stroke risk associated with aPLs, 24,25 but later studies that included larger numbers of patients failed to find such an association. 8,26 The Antiphospholipid Antibodies and Stroke Study (n=1770), a prospective cohort study, reported that immunoreactivity to either aCL or lupus anticoagulant antibodies at the time of a first ischemic stroke did not influence the risk of subsequent thrombo-occlusive events over the following 2 years.…”
Section: November 2016mentioning
confidence: 99%
“…In consecutive patients with aPLs and focal cerebral ischaemia, cerebral infarctions within the first follow-up year supported the data that IgG aCL represented a risk factor for recurrent stroke. 13 In a later study this was confirmed, and the subsequent thrombo-occlusive events were associated with IgG aCL (most frequently in patients with aCL 40 GPL), thus confirming the role of aCL as a risk factor for recurrent stroke.…”
Section: As Mentioned Inmentioning
confidence: 65%